2016
DOI: 10.1186/s13063-016-1588-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of three fasting plasma glucose targets for insulin glargine-based therapy in people with type 2 diabetes mellitus in China: study protocol for a randomized controlled trial

Abstract: BackgroundA large proportion of patients with T2DM in China do not meet accepted HbA1c targets despite the availability of guidelines that describe a treatment pathway for achieving glycemic control. The aim of this study is to identify the fasting plasma glucose (FPG) target that will provide the highest control rate of HbA1c <7 % in Chinese patients with T2DM treated with an insulin glargine-based regimen as an adjunct to an established OAD regimen. This information will support improvements in diabetes care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This was a 24 week, open‐label, parallel‐group, randomized, treat‐to‐target study (http://clinicaltrials.gov identifier: NCT02545842). The study design and methods have been reported previously . Briefly, eligible patients were between 18 and 65 years of age, had a diagnosis of T2D, with HbA1c >7% to ≤10.5% despite stable doses of one to three oral anti‐hyperglycaemic drugs (OADs) for at least 3 months, had fasting plasma glucose (FPG) of >7 mmol/L, had a body mass index of ≥20 to ≤40 kg/m 2 , had a duration of diabetes of at least 1 year, and were willing to initiate treatment with basal insulin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a 24 week, open‐label, parallel‐group, randomized, treat‐to‐target study (http://clinicaltrials.gov identifier: NCT02545842). The study design and methods have been reported previously . Briefly, eligible patients were between 18 and 65 years of age, had a diagnosis of T2D, with HbA1c >7% to ≤10.5% despite stable doses of one to three oral anti‐hyperglycaemic drugs (OADs) for at least 3 months, had fasting plasma glucose (FPG) of >7 mmol/L, had a body mass index of ≥20 to ≤40 kg/m 2 , had a duration of diabetes of at least 1 year, and were willing to initiate treatment with basal insulin.…”
Section: Methodsmentioning
confidence: 99%
“…However, the proportion of patients who achieved HbA1c <7% without hypoglycaemia (glucose ≤3.1 mmol/L) was the same in the two target groups . The present study was designed to evaluate the effect of three pre‐defined FBG targets on the proportion of Chinese patients with T2D who achieved HbA1c <7.0% . The FBG targets to which patients were randomized were 3.9 < FBG ≤7.0, 3.9 < FBG ≤6.1 and 3.9 < FBG ≤5.6 mmol/L.…”
Section: Introductionmentioning
confidence: 99%
“…The study design and methods for the FPG GOAL study (ClinicalTrials.gov identifier NCT02545842) have been reported previously [ 23 , 24 ]. Briefly, FPG GOAL enrolled individuals with T2D and an HbA1c > 53 mmol/mol (> 7.0%) to ≤ 91 mmol/mol (≤ 10.5%) and FPG > 7 mmol/L despite receiving stable doses of 1–3 OADs for at least 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…The primary endpoint of FPG GOAL study was the proportion of participants achieving an HbA1c < 53 mmol/mol (< 7%) at 24 weeks [ 23 , 24 ]. Secondary endpoints included the change from baseline in HbA1c, FPG, PPG and PPG excursions, body weight and BMI at 24 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and methods for the FPG GOAL study (ClinicalTrials.gov identifier NCT02545842) have been reported previously [8,9]. Briefly, FPG GOAL included individuals aged 18-65 years with T2D, with HbA1c levels between [ 7% and B 10.5%, were inadequately controlled with stable doses of 1-3 oral antidiabetic drugs (OADs) for C 3 months, had fasting plasma glucose (FPG) of [ 7 mmol/L, a body mass index of C 20 to B 40 kg/m 2 , with duration of diabetes of at least 1 year and those who were willing to start treatment with basal insulin.…”
Section: Study Design and Participantsmentioning
confidence: 99%